Safety of two different doses of simvastatin plus rifaximin in decompensated cirrhosis (LIVERHOPE-SAFETY): a randomised, double-blind, placebo-controlled, phase 2 trial. (January 2020) - Pose, Elisa; Napoleone, Laura; Amin, Ahmed; Campion, Daniela; Jimenez, César; Piano, Salvatore; Roux, Olivier; Uschner, Frank Erhard; de Wit, Koos; Zaccherini, Giacomo; Alessandria, Carlo; Angeli, Paolo; et al.
Summary: Background: Statins have beneficial effects on intrahepatic circulation and decrease portal hypertension and rifaximin modulates the gut microbiome and might prevent bacterial translocation in patients with cirrhosis. Therefore, this drug combination might be of therapeutic benefit in patients with decompensated cirrhosis. However, there is concern regarding the safety of statins in patients with decompensated cirrhosis. We assessed the safety of two different doses of simvastatin, in combination with rifaximin, in patients with decompensated cirrhosis. Methods: We did a double-blind, randomised, placebo-controlled, phase 2 trial in patients with decompensated cirrhosis and moderate-to-severe liver failure from nine university hospitals in six European countries (Italy, France, Holland, Germany, the UK, and Spain). Patients older than 18 years with Child-Pugh class B or C disease were eligible. We randomly assigned patients (1:1:1) to receive either simvastatin 40 mg/day plus rifaximin 1200 mg/day, simvastatin 20 mg/day plus rifaximin 1200 mg/day, or placebo of both medications for 12 weeks. Randomisation was stratified according to Child-Pugh class (B vs C) and restricted using blocks of multiples of three. The primary endpoint was development of liver or muscle toxicity, as defined by changes in liver aminotransferases (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]), alkaline phosphastase, and creatine kinase. The study is registered with the European Union Clinical Trials Register, 2016-004499-23, and with ClinicalTrials.gov, NCT03150459 . Findings: The study recruitment period was between July 28, 2017, and Jan 2, 2018. Follow-up finished on March 12, 2018. 50 patients were randomly assigned to simvastatin 40 mg/day plus rifaximin 1200 mg/day (n=18), simvastatin 20 mg/day plus rifaximin 1200 mg/day (n=16), or placebo of both medications (n=16). Six patients (two from each group) were excluded. Therefore, the full analysis set included 44 patients (16 in the simvastatin 40 mg/day plus rifaximin 1200 mg/day group, 14 in the simvastatin 20 mg/day plus rifaximin mg/day group, and 14 in the placebo group). After a safety analyses when the first ten patients completed treatment, treatment was stopped prematurely in the simvastatin 40 mg/day plus rifaximin group due to recommendations by the data safety monitoring board. Patients in the simvastatin 40 mg/day plus rifaximin group showed a significant increase in AST and ALT compared with the placebo group (mean differences between the groups at the end of treatment for AST 130 IU/L [95% CI 54 to 205; p=0·0009] and for ALT 61 IU/L [22 to 100; p=0·0025]. We observed no significant differences at 12 weeks in AST and ALT between the simvastatin 20 mg/day plus rifaximin and placebo group (for AST −14 IU/L [–91 to 64; p=0·728] and for ALT −8 IU/L [–49 to 33; p=0·698]). We observed no significant differences in alkaline phosphatase between the the simvastatin 40 mg/day plus rifaximin or the simvastatin 20 mg/day plus rifaximin groups compared with placebo. Patients in the simvastatin 40 mg/day plus rifaximin group showed an increase in creatine kinase at the end of treatment compared with patients in the placebo group (1009 IU/L [208 to 1809]; p=0·014). We observed no significant changes in creatine kinase in the simvastatin 20 mg/day plus rifaximin group (4·2 IU/L [–804 to 813]; p=0·992). Three (19%) patients in the simvastatin 40 mg/day group developed liver and muscle toxicity consistent with rhabdomyolysis. The number of patients who stopped treatment because of adverse events was significantly higher in the simvastatin 40 mg/day plus rifaximin group (nine [56%] of 16 patients) compared with the other two groups (two [14%] of 14 for both groups; p=0·017). There were no serious unexpected adverse reactions reported during the study. Interpretation: Treatment with simvastatin 40 mg/day plus rifaximin in patients with decompensated cirrhosis was associated with a significant increase in adverse events requiring treatment withdrawal, particularly rhabdomyolysis, compared with simvastatin 20 mg/day plus rifaximin. We recommend simvastatin 20 mg/day as the dose to be used in studies investigating the role of statins in patients with decompensated cirrhosis. Funding: Horizon 20/20 European programme.